Validating of the pre-clinical mouse model for metastatic breast cancer to the mandible - Young Sun HWANG; Sang-Sun HAN; Ki-Rim KIM; LEE Ye-Jin; LEE Sun-Kyung; PARK Kwang-Kyun; CHUNG Won-Yoon (University of São Paulo, 2015)
Metastatic breast carcinoma has a great tendency to spread to the mandible. It is concomitantly associated with bone destruction, food intake disorder, and a poorer prognosis. Appropriate animal models need to be developed for a better understanding of the mechanisms underlying the metastatic process of breast cancer cells to mandible and to test the effects of potential lead compounds. Here, we assessed the metastasis model of intracardiac injection using luciferase-transfected metastatic breast cancer cells (MDA-MB-231Luc+) by determining the incidences of metastasis, mCT images, and histopathological results. A high bioluminescence signal mainly detected mandibular lesions with less frequent distal femora and proximal tibiae lesions. Extensive mandibular bone destruction occurred in nude mice grafted with metastatic breast cancer cells. This type of animal model might be a useful tool in assessing therapeutic implications and the efficacy of anti-cancer drugs for osteolytic cancers.